2023
DOI: 10.3390/nu15194274
|View full text |Cite
|
Sign up to set email alerts
|

The Southern European Atlantic Diet and Its Supplements: The Chemical Bases of Its Anticancer Properties

Pablo García Vivanco,
Pablo Taboada,
Alberto Coelho

Abstract: Scientific evidence increasingly supports the strong link between diet and health, acknowledging that a well-balanced diet plays a crucial role in preventing chronic diseases such as obesity, diabetes, cardiovascular issues, and certain types of cancer. This perspective opens the door to developing precision diets, particularly tailored for individuals at risk of developing cancer. It encompasses a vast research area and involves the study of an expanding array of compounds with multilevel “omics” compositions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 186 publications
0
2
0
Order By: Relevance
“…A recent study [ 44 ] showed the cytotoxic effects of C. annuum extracts on various tumor cell lines: breast cancer (MDA-MB-231 and MCF-7), pancreatic cancer (PANC-1, pancreatic ductal adenocarcinoma), skin cancer (A375, human melanoma), and lymphoblastic (K562, myelogenous leukemia). The highest cytotoxicity (IC 50 = 153.18 µg/mL) was recorded on PANC-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study [ 44 ] showed the cytotoxic effects of C. annuum extracts on various tumor cell lines: breast cancer (MDA-MB-231 and MCF-7), pancreatic cancer (PANC-1, pancreatic ductal adenocarcinoma), skin cancer (A375, human melanoma), and lymphoblastic (K562, myelogenous leukemia). The highest cytotoxicity (IC 50 = 153.18 µg/mL) was recorded on PANC-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…These methods were employed to predict the binding affinity of the molecules to a protein known as ERK2, which is associated with skin cancer. 31–34 It should be noted that the selection of ERK2 as the target protein for investigating benzophenazine enaminone derivatives as inhibitors is grounded in its significance in cancer, suitability for drug targeting, prior research outcomes, and specificity. This choice represents a logical and scientifically justified strategy in the endeavor to develop potential therapeutic agents for treating cancer.…”
Section: Introductionmentioning
confidence: 99%